The Importance of Sulfur for Florida Agricultural Production - Lakesh K. Sharma; Lincoln Zotarelli; Christian T. Christensen (EDIS)
Intended for Extension clients, this publication highlights the importance of sulfur in row and vegetable crop production systems in Florida, such as its use in pesticides and fertilizers. Additionally, the publication provides insights into the perspective of the Environmental Protection Agency (EPA) on sulfur in naturally occurring aquatic systems. This publication's target audience is agricultural producers, Extension agents, crop consultants, representatives of the fertilizer industry, state and local agencies, students, instructors, researchers, and interested Florida citizens.